Modernism and the making of the Soviet New Man - Vujošević, Tijana (Book collections on Project MUSE., 2017)
Modernism and the Making of the New Man is a history or Soviet architecture that is unique in that, instead of styles or great architects, it focuses on the design of communist subjectivity - the notion of the ""new man"". This perspective is key to understanding the dynamic and changing relationship between official communist culture and its idiosyncratic interpretations in the domain of the personal and the quotidian.